Challenges and opportunities for police data collection: an examination of three Caribbean police departments - Lancaster-Ellis, Karen (The Palgrave handbook of Caribbean criminology, 2024)
In the Caribbean, poor data quality besieges some police departments and evidence exists of limited, inaccurate, missing, tardy, and archaic data collection methods; a dual system of data collection; difficulties in accurately assessing, comparing, and contrasting past performance with current performance; making future projections and the inability to fully adopt an evidence-based approach. International agencies struggle in determining the police output levels; in making funding decisions and assessing their needed support. Consequently, the validity and reliability of police data is diminished, inconsistent, and cannot be used for comparability or analysis. This qualitative study examines data collection in three Caribbean police departments. Semi-structured interviews were conducted with officers involved in or familiar with their agency’s data collection processes. Questions will be based on constructs relating to data collection and their challenges. The findings will have implications for future research and recommendations will be advanced to improve data collection throughout the Caribbean.